Natural treasures from Picrorhiza kurrooa: a computational exploration of drug-like properties and bioactivity of kutkin, cucurbitacin, apocynin and lupanine - Britto, G. Francis; Subash, K. R.; Nagamani, N. (International Journal of Basic & Clinical Pharmacology, 2024)
Background: To analyse and predict the basic pharmacokinetic and toxicological properties of four compounds of interest found in Picrorhiza kurroa (Kutkin, cucurbitacin, apocynin and lupanine) using computational bioinformatics tools. Methods: The chemical structures and molecular properties of the compounds were obtained from authentic sources and processed for data profiling. 2D structures were converted to 3D structures using ChemSketch software and PHASE module. In silico screening of the 3D structures was performed using bioinformatics prediction software to assess drug-likeness, absorption, blood-brain barrier penetration, enzyme interaction potential, skin penetration, and acute oral toxicity. Results: Kutkin exhibited poor drug-likeness and low oral absorption, while the other three compounds showed promising drug-like properties and good oral absorption. Cucurbitacin and lupanine were predicted to cross the blood-brain barrier, while Kutkin and Apocynin were not. None of the compounds were substrates for P-glycoprotein, but Kutkin and cucurbitacin were substrates for CYP3A4. All four compounds had low skin penetration. Acute oral toxicity varied, with cucurbitacin classified as highly toxic and the others as slightly toxic. Conclusions: Cucurbitacin, apocynin, and lupanine have potential for further development as therapeutic agents due to their favorable drug-like properties and good absorption. Kutkin’s poor drug-likeness and low absorption make it less suitable for oral drug development. This information provides valuable insights for further research on the medicinal properties of Picrorhiza kurroa and the development of new drugs based on its active compounds.